PRODUCTION OF CARBON MATERIALS BY CONJUNCTION OF HYDROTHERMAL AND ACTIVATION PROCESSES - Valente Nabais, Joao (2013)
Activated Carbons (AC) are traditionally produced by chemical or physical activation processes, frequently using biomass materials as precursors [1]. These procedures can be modified in order to create particular surface characteristics (both textural and chemical), so that the adsorption of a given organic or inorganic compound is optimized. Recently, the use of hydrothermal carbonization processes (HTC) to produce carbon nanomaterials was reported [2]. This process consists in the treatment of a material in water under soft temperature conditions (in the range 150-350ºC) and in some cases under pressure conditions. The HTC processes are very attractive due to its simplicity, cheapness and efficiency; they can also be classified as “green” since it does not involves organic solvents, catalysts or surfactants. By HTC, the biomass organic components are broken up and dissolved in the water, and a carbon rich solid product is obtained (the hydrochar) as well as a liquid phase containing sugars and/or oligomers that can be used for a variety of practical purposes. Previous works have reported that during HTC oxygen accumulates at the periphery of the particles originating a final carbonaceous material with a core–shell structure composed of a hydrophobic core and a hydrophilic shell containing a large number of reactive oxygen functional groups [3]. We have published in a recent work the production of hydrochars with acidic properties [4], which implies an interesting novelty regarding the surface chemistry when compared with chars obtained by pyrolysis that have basic characteristics. Taking into account these results we have explored the possibility of using the hydrochars to produce ACs with controlled surface chemistry and porosity by physical activation with air and carbon dioxide. As precursors we used three biomass resources, which are very abundant in the Southern part of Iberian Peninsula: walnut shell, sunflower stem and olive stone.